Pengembangan E-book KATABAH (Kalimat Tayyibah) Berbasis Heyzine Flipbook Pada Pembelajaran PAI di Kelas III SD - Gia, Gia Lavenia; Faizal, Faizal Fasawiguna; Putri, Putri Wulandari; Ani, Ani Nur Aeni (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
The purpose of this research is to develop digital learning media in the form of E-Books as a tool for teachers in providing PAI learning materials to third grade elementary school students. The development of the KATABAH E-Book was carried out through the D&D model consisting of the stages of problem identification, describing objectives, product design and development, product trials, trial evaluation, and communication of test results. These stages involve observation, interviews, student and material analysis, and product testing. The results showed that the KATABAH E-Book received a positive response from third grade students. Aspects such as conciseness of material, clarity of sentences, attractive design, ease of understanding the material, and accessibility of media were rated well by students. This shows that the KATABAH E-Book based on Heyzine Flipbook is feasible to use as an effective learning media in understanding thayyibah sentences in grade III SD.